A novel adsorptive ceramic membrane for efficient strontium removal. (October 2020) - Almasri, Dema A.; Kayvani Fard, Ahmad; McKay, Gordon; Kochkodan, Viktor; Atieh, Muataz A.
Graphical abstract: Highlights: Activated carbon (AC) was doped with Fe to enhance strontium adsorption. Hybrid ceramic membranes incorporated with AC-Fe nanocomposites were prepared. Al2 O3 /AC/Fe ceramic membranes showed more than 90 % strontium removal from water. Hybrid membranes removed 80 % of strontium from treated sewage effluent. Abstract: In this paper activated carbon (AC) was doped with iron oxide (Fe2 O3 ) nanoparticles and characterized and tested for its adsorptive efficiency towards strontium by varying the contact time, pH and strontium concentration in the feed solutions. The modified adsorbent (AC-Fe) proved to be far more effective than raw AC for strontium adsorption. Based on these results, novel hybrid ceramic membranes were prepared by incorporating AC and AC-Fe nanocomposites into an alumina (Al2 O3 ) matrix via mixing-casting-sintering method. The pristine Al2 O3, Al2 O3 /AC, and hybrid Al2 O3 /AC/Fe membranes were characterized and tested for strontium rejection. The incorporation of AC-Fe nanocomposites into the Al2 O3 membrane matrix notably affected the average pore size, hydrophilicity and adsorption capabilities of the prepared membranes. The Al2 O3 /AC/Fe membrane was shown to be far superior relative to the pristine Al2 O3 membrane and the Al2 O3 /AC membrane in terms of flux and strontium removal efficiencies at various pH values and strontium concentrations in the feed. Approximately 90 % of strontium was removed at a pH 7 and at a feed concentration of 2 mg/L. The Al2 O3 /AC/Fe membrane, when tested with real treated sewage effluent, exhibited more than 80 % removal of strontium from wastewater.